1998
DOI: 10.3892/ijmm_00000071
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CCR5-Δ32 deletion in human immunodeficiency virus type 1 (HIV-1) in healthy blood donors, HIV-1-exposed seronegative and HIV-1-seropositive individuals of southern Brazilian population

Abstract: Abstract. The frequency of CCR5-Δ32 allele in human immunodeficiency virus type 1 (HIV-1) infection in the southern Brazilian population was determined in a crosssectional study carried out from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The CCR5-∆32 allele has been found in Brazilian populations in frequencies between 2.2-6.8% (Munerato et al 2003, Vargas et al 2006, Reiche et al 2008, Rigatto et al 2008. Here, we found a frequency of 2.4%.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The CCR5-∆32 allele has been found in Brazilian populations in frequencies between 2.2-6.8% (Munerato et al 2003, Vargas et al 2006, Reiche et al 2008, Rigatto et al 2008. Here, we found a frequency of 2.4%.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, in another study conducted in Southern Brazil, the CCR5-∆32 frequency was 2.9% among HIV-1 seropositive patients with AIDS, 5.6% among those seropositive and asymptomatic, 5.6% in healthy blood donors and 5.51% in HIV-1-exposed seronegative subjects. CCR5-Δ32 allelic frequencies were not different when the self-reported racial characteristics of the individuals evaluated were considered (Reiche et al 2008). This allele has not been found among South American native Indians, corroborating the hypothesis of a european origin of this allele and its introduction to the continent through migration (Leboute et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of the infection progression is regulated by the balance between host and viral factors. Human allelic variants do not only interfere in the susceptibility to HIV-1 infection, but also in the subsequent rates of disease progression towards AIDS [13][14][15][16][17][18][19]. Regarding the association of the CHS with HIV-1, studies have reported that the secretory pathway in CD4 + T cells supports HIV-1 cell-to-cell spread at the virological sinapse [20,21].…”
Section: Case Descriptionmentioning
confidence: 99%
“…Studies investigating serodiscordant couples have previously described some factors associated with protection among HESN, such as the presence of the 32-base-pair (bp) deletion in chemokine CC receptor 5 (CCR5D32), 2 differences in T cell reactivity to HIV, 3 and the presence of cationic peptides in cervicovaginal secretions. 4 Although Brazil has the largest number of HIV-infected people among the countries in Central and South America, 5 and an ethnically very diverse population, 6 there is a paucity of information regarding cohorts of serodiscordant couples.…”
mentioning
confidence: 99%